Canadian residents’ perceptions of cross-cultural care training in graduate medical school - Singh, Barinder; Banwell, Emma; Groll, Dianne Leonie (Canadian Medical Education Journal, 2017)
Background: The Royal College of Physicians and Surgeons of Canada specifies both respect for diversity as a requirement of professionalism and culturally sensitive provision of medical care. The purpose of the present study was to evaluate the perception of preparedness and attitudes of medical residents to deliver cross-cultural care. Methods: The Cross Cultural Care Survey was sent via e-mail to all Faculty of Medicine residents (approx. 450) in an academic health sciences centre. Comparisons were made between psychiatry residents, family medicine residents, and other residency groups with respect to training, preparedness, and skillfulness in delivering cross-cultural care. Results: Seventy-three (16%) residents responded to the survey. Residents in psychiatry and family medicine reported significantly more training and formal evaluation regarding cross-cultural care than residents in other programs. However, there were no significant differences in self-reported preparedness and skillfulness. Residents in family medicine were more likely to report needing more practical experience working with diverse groups. Psychiatry residents were less likely to report inadequate cross-cultural training. Conclusion: While most residents reported feeling skillful and prepared to work with culturally diverse groups, they report receiving little additional instruction or formal evaluation on this topic, particularly in programs other than psychiatry and family medicine.